(untitled) (Research, Society and Development, 2021)
This work aimed to present the main effects of mindfulness in pregnant women that are being researched in the last 10 years (2010-2020). In this sense, we sought, through a Systematic Literature Review (RSL), to retrieve and evaluate scientific studies that present some contribution in the evaluation of the main effects of this alternative therapy in pregnant women, in which gestational trimester this technique is most studied and in which gestational risk (high or low risk) of most pregnant women studied. For this, data were collected and organized from PubMed and BVS (Virtual Health Library) databases, both widely accepted by the Brazilian medical academy. The results show that the most prevalent effects in the studies analyzed are those of a psychological nature, with the reduction of depressive symptoms being the main ones. However, physical and behavioral effects were also found in the studied pregnant women. In addition, these pregnant women were experiencing the 2nd trimester of pregnancy and were mostly classified as low risk.